Lactobacillus reuteri Promotes Intestinal Development and Regulates Mucosal Immune Function in Newborn Piglets - Wang, Minjuan; Wu, Haiqin; Lu, Linhao; Jiang, Lan; Yu, Qinghua (Frontiers in Veterinary Science, 2020)
Intestinal microbiota is necessary for the guarantee of intestinal mucosal barrier. However, the detailed effect of probiotics on porcine intestinal development, especially in the early life, is still unclear. In this study, we treated 3-day-old newborn piglets with Lactobacillus reuteri (L. reuteri) D8 and observed its beneficial effect on piglets. The body weights, villus height, and crypt depth of jejunum were all significantly increased after L. reuteri treatment in piglets. L. reuteri also significantly increased the proliferation index of PCNA+ cells in the crypt, as well as c-Myc and Tcf4 expressions. Furthermore, L. reuteri also enhanced intestinal mucosal barrier with the increase of goblet cells and antimicrobial peptides (AMPs) expressions of Muc2, Lyz1, and pBD1. The well development of Peyer's patches and increased number of CD3+ T cells, combined with increased expression of IL-4 and IFN-γ, also demonstrated the immune stimulation effect of L. reuteri D8. This study demonstrated that L. reuteri promotes the development of intestine mucosal system and maintains intestinal mucosal barrier in newborn piglets.